Building Nation Character Through Hafiz Program in SMP Islam Terpadu al-Anis Kartasura - Wicagsono, Muhammad Arif; Hidayat, Syamsul (Muhammadiyah University Press, 2018)
Character education is an effort to fortify and improve the noble and fundamental values of life so as to build a person with a distinctive or special character. It also seeks to build harmonious relationships between a person with family and society in undergoing the role of character education on a collective basis. Furthermore, a range of methods are employed to conduct such an education, including through the program of Qurâan memorization or known as Hafiz. This study aims to find the relevance of the program in fostering the noble character of the nation. It used qualitative descriptive approach, with observation and in-depth interview as data collection methods. Data analysis technique was the inter-method comparative analysis, which was applied in memorizing the Qurâan. This study was conducted at SMP Al-Anis Kartasura, Central Java, Indonesia. The study found there are various methods for memorizing the Qurâan, such as Yanbuâa, Tikrar, Muri-Q, and Qiraâati. The characters instilled in the program include religious, disciplined, honest, curios, bibliophilic, responsible, creative, appreciative, and friendly/communicative.